1999
DOI: 10.1002/j.1551-8833.1999.tb08601.x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic treatment considerations

Abstract: The least‐cost method of removing arsenic may not be the best method all around. The best arsenic treatment technique for a given utility will depend on arsenic concentration and species in source water, other constituents in the water, existing treatment processes, treatment costs, and handling of residuals. To evaluate these issues, a national survey investigated arsenic occurrence and speciation in US drinking water sources. In general, total arsenic concentration was higher in groundwater than in surface w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 27 publications
1
70
0
Order By: Relevance
“…Enhanced coagulation, is intended to improve natural organic matter (NOM) removal, but is also in many cases the least-cost option for water utilities to comply with the new As MCL [6,7]. Early bench, pilot, and demonstration scale studies have shown that As(V) can be efficiently removed during coagulation with ferric chloride and alum even when present at low or high concentration in influent waters [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced coagulation, is intended to improve natural organic matter (NOM) removal, but is also in many cases the least-cost option for water utilities to comply with the new As MCL [6,7]. Early bench, pilot, and demonstration scale studies have shown that As(V) can be efficiently removed during coagulation with ferric chloride and alum even when present at low or high concentration in influent waters [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned patterns of behaviour of arsenic in waters were also observed in another temperate low-contaminated river, the Adour by Point et al (2007). The relationship between dissolved and particulate arsenic was highly dependent on flow but during annual average flow it was 1:1, as described in one third of 49 groundwater sources in USA (Chen et al, 1999).…”
Section: Discussion 41 the Fluvial Reservoirmentioning
confidence: 55%
“…Removal efficiency with reverse osmosis units has been shown to be lower when arsenic is present as As (III) (Chen et al 1999;USEPA 2000;Walker et al 2008).…”
Section: Significance Of Trivalent Arsenic (As (Iii) )mentioning
confidence: 99%